Factors Affecting Consumers’ Perception towards E-Payment Systems in India - Saini, Gurmeet Singh; Sharma, Sushil (Indian Journal of Computer Science, 2017)
Demonetization by Government of India is a well-planned move towards a cashless economy which came as a bonanza for several digital payment platforms. Various mobile wallets and online payment systems are sprouting to reap the benefits of this opportunity. These vibrant payment systems evaporate the importance of cash as the only method of exchange of value. Perception of consumers towards these payment systems is highly important for future growth. This study aims to discover perception of users towards electronic payment (e-payment). Literature review indicates that factors such as usefulness, ease of use, security, trust, and risk significantly affect users’ perception. A conceptual model was developed and tested in this study mainly focusing on factors influencing users’ perception towards e-payment. A self-administered questionnaire was developed and disseminated to 200 respondents out of which 150 valid responses were considered for further analysis. Cronbach alpha was used to check the reliability of the questionnaire. Exploratory factor analysis was used to extract the variables. Correlation and multiple regression analysis revealed that usefulness, ease of use, and security significantly impact perception of users towards e-payment. However, results for trust and risk are insignificant. It has been found out that there is a great potential for future expansion of such payment instruments and the challenge is to meet the continuously growing expectations of consumers. Several implications can be drawn from the study for both marketing managers and policy makers which help in developing strategies directed at increasing epayment acceptance, and usage.